1988
DOI: 10.1136/jnnp.51.3.403
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the number of motor units based on macro-EMG.

Abstract: SUMMARYThe technique of the macro-EMG was used to estimate the number of motor units in the tibialis anterior muscles of healthy subjects in a wide range of ages, and of patients with myasthenia gravis and patients with amyotrophic lateral sclerosis or spinal muscular atrophy. The results obtained suggest a decrease in the number of motor units in the tibialis anterior muscle with increasing age in normal subjects. In myasthenic patients the motor unit count was within the normal range for their age group. Pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
27
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 22 publications
2
27
0
1
Order By: Relevance
“…21,60,93 The macro-EMG technique has shown an increase in MU size in the vastus lateralis, the tibialis anterior, and the biceps brachii from subjects older than age 60 years, indirectly indicating an increased number of muscle fibers per motor unit. 15,79,80 At the microscopic level of muscle analysis, there is evidence of age-related neuropathic changes, such as small angulated fibers and grouped atrophy, in samples from old or very old individuals. 26,45,54,56,76,85,86 In comparisons between older adults and young subjects, whole muscle analysis via cadaveric or radiological observations has shown that thigh and leg muscles undergo significant size reductions over time, 33,34,44,56,91 which are consistent in timing and magnitude to the loss of strength.…”
Section: Age-related Loss Of Functional Cells From the Motor Systemmentioning
confidence: 99%
“…21,60,93 The macro-EMG technique has shown an increase in MU size in the vastus lateralis, the tibialis anterior, and the biceps brachii from subjects older than age 60 years, indirectly indicating an increased number of muscle fibers per motor unit. 15,79,80 At the microscopic level of muscle analysis, there is evidence of age-related neuropathic changes, such as small angulated fibers and grouped atrophy, in samples from old or very old individuals. 26,45,54,56,76,85,86 In comparisons between older adults and young subjects, whole muscle analysis via cadaveric or radiological observations has shown that thigh and leg muscles undergo significant size reductions over time, 33,34,44,56,91 which are consistent in timing and magnitude to the loss of strength.…”
Section: Age-related Loss Of Functional Cells From the Motor Systemmentioning
confidence: 99%
“…Although developed decades ago, 18,25,33,49,58 quantitative techniques have rarely been used in clinical neurophysiology to date. There is little indication in a traditional clinical neurophysiology practice, but several of the methods have been liberally applied in research over the years, mainly to observe changes over time.…”
Section: Clinical Assessmentmentioning
confidence: 99%
“…Isolating the target muscle can be achieved by recording with the needle electrode shaft (macro-EMG, 50 Conmac, 28 or concentric cannula) rather than the surface electrode. At our center, we have used a macro-EMG needle (macro-MUNE), described and validated by de Koning et al in 1988 18 using the spike-triggered average 3,5 (STA) MUNE approach. If the muscle is large, then we sample at intervals of 0.5 cm perpendicular to the motor point.…”
Section: Donor Nerve: Neurophysiological Evaluationmentioning
confidence: 99%
“…Estudos que utilizaram eletromiografia (STALBERG, 1980) ou técnicas para estimar o número de unidades motoras (DOHERTY et al, 1995) demonstraram perdas substanciais das unidades motoras ativas em músculos das extremidades superiores e inferiores. (DEKONING et al, 1988;BROWN, 2002). Esse processo é apontado como outro importante fator em explicar a perda de força muscular característica do avançar da idade.…”
Section: Discussionunclassified